Depth‐sensing indentation and nano‐dynamic mechanical properties of aluminum nitride nanoparticles reinforced high density poly‐ethylene nanocomposites. Issue 1 (8th November 2017) - Rajeshwari, P.; Rao, V.V.; Dey, T.K.
Abstract : Inorganic aluminum nitride (AlN) nanoparticles offer numerous innovative applications in the field of electronic packaging due to its outstanding features; viz., high mechanical strength, stable crystal structure, excellent thermal conductivity, low coefficient of thermal expansion, low‐cost, and non‐toxicity. In this research, attempts have been made to investigate the effect of reinforcement of nano‐AlN particles in high density poly‐ethylene (HDPE) thermoplastic polymer on their nano‐mechanical properties using depth‐sensing indentation (DSI) technique. Polymer‐matrix nanocomposites composed of pure HDPE and 1–20 vol% nano‐AlN/HDPE composites are prepared via melt mixing followed by compression molding. Surface‐morphology and crystallinity of HDPE/nano‐AlN composites are characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), and differential scanning calorimetry (DSC). Nano‐scale hardness, modulus of elasticity, storage modulus, and loss tangent ( tanδ ) of HDPE/nano‐AlN composites have been evaluated using static and dynamic‐DSI. Both static and dynamic‐DSI results indicate that with increasing concentration of AlN nanoparticles in pristine HDPE, the nano‐mechanical properties display significant improvement. Results are discussed in relation to the surface‐morphology, crystallinity and interfacial adhesion between pure HDPE and nano‐AlN particles. A comparison between nano‐mechanical data extracted from static‐DSI and dynamic‐DSI techniques analysis is also attempted. POLYM. COMPOS., 40:240–254, 2019. © 2017 Society of Plastics Engineers